Decentralization and local public services in Ghana: Do geography and ethnic diversity matter? - Akramov, Kamiljon T.; Asante, Felix Ankomah (International Food Policy Research Institute, 2009)
This paper explores disparities in local public service provision between decentralized districts in Ghana using district- and household-level data. The empirical results show that districts' geographic locations play a major role in shaping disparities in access to local public services in Ghana. Most importantly, the findings suggest that ethnic diversity has significant negative impact in determining access to local public services, including drinking water. This negative impact is significantly higher in rural areas. However, the negative impact of ethnic diversity in access to local public services (drinking water) decreases as average literacy level increases. The paper relates the results to literature and discusses policy implications of main findings.